An oxygen‐tolerant photo‐induced metal‐free reversible addition‐fragmentation chain transfer polymerization. Issue 21 (2nd October 2018) - Yu, Lei; Wei, Yanlong; Tu, Yuanyuan; Lin, Shudong; Huang, Zhenzhu; Hu, Jiwen; Chen, Yue; Qiao, Hang; Zou, Wei
ABSTRACT: We report herein a visible light‐induced metal‐free living polymerization with high oxygen tolerance that can be performed in aqueous media. In contrast with ordinary living/controlled radical polymerizations, oxygen can be present throughout the entire reaction process. This reaction can be photo‐induced and proceeds at room temperature. First, we have successfully synthesized a well‐defined polymer in an ambient atmosphere by the photo‐induced radical polymerization method, using acrylic acid as a monomer and fluorescein as a photocatalyst. However, the subsequent chain extension reaction did not occur, possibly due to oxidation of the chain transfer agent (CTA). Despite this, we found that the addition of vitamin C (ascorbic acid) imparted the process with oxygen tolerance. We conducted a systematic study to optimize the best concentrations of the key reagents including the monomer, CTA, fluorescein, and vitamin C. Through these optimizations we were able to synthesize in the presence of oxygen a series of well‐defined poly(acrylic acid)s (PAAs) with dispersities ( Ð ) below 1.3 and molecular weights that closely matched the theoretical values. The kinetic study showed that the molecular weight of the produced PAA increased linearly with the conversion of the monomer, and chain extension reaction also yielded a block polymer with a higher molecular weight than that of the previous polymer. Therefore, we developed a novel photo‐induced living polymerization method that can be conducted both in the absence of oxygen and in the presence of air. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2437–2444 Abstract : An oxygen‐tolerant photo‐induced metal‐free RAFT polymerization was successfully developed and optimized.